2005
DOI: 10.2527/2005.83102255x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of pig breeds from Korea and China using microsatellite loci analysis1

Abstract: To understand molecular genetic characteristics of Korean pigs, the genetic relationships of nine pig breeds including two Korean pigs (Korean native pig and Korean wild pig), three Chinese pigs (Min pig, Xiang pig, and Wuzhishan pig), and four European breeds (Berkshire, Duroc, Landrace, and Yorkshire) were characterized from a 16-microsatellite loci analysis. The mean heterozygosity within breeds ranged from 0.494 to 0.703. Across multiple loci, significant deviation from Hardy-Weinberg equilibrium was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
54
5
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 37 publications
19
54
5
4
Order By: Relevance
“…This observation was congruent with Fang et al [12] and Kim et al [22] and was in line with the biogeography of the wild boar, that occurs throughout Eurasia but is absent in the desert areas in the Gobi and at high altitudes in the Himalayas [31]. This effectively presented a barrier for dispersion in what is currently the central Asian part of China (i.e.…”
Section: Chinese Breeds: Clusteringsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation was congruent with Fang et al [12] and Kim et al [22] and was in line with the biogeography of the wild boar, that occurs throughout Eurasia but is absent in the desert areas in the Gobi and at high altitudes in the Himalayas [31]. This effectively presented a barrier for dispersion in what is currently the central Asian part of China (i.e.…”
Section: Chinese Breeds: Clusteringsupporting
confidence: 90%
“…A comprehensive, global assessment of pig diversity would give better insight into the genetic relationships and distinctiveness of pigs from different parts of the world, and may aid in preservation of worldwide livestock diversity. Recent papers have reported on relations between pigs using microsatellite markers [12,22,26,28,40,47,50], but mainly between pig breeds from either China or Europe. For instance, Zhang et al [50] concluded that a number of major groups could be discerned, in part congruent with previous classification schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Number of alleles and allelic size range were compared to Korean, Chinese and Iberian pig breeds. Number of alleles for marker SO072 (7), SO070 (15), SW936 (10), SW24 (13) were similar to Iberian as well as Korean and Chinese population described by Fabuel et al (2004) and Kim et al (2005). Markedly higher number of alleles for each microsatellite markers described above was observed in Chinese indigenous pig breeds (Yang et al 2003).…”
Section: Resultssupporting
confidence: 66%
“…The observed heterozygosity varied between 0.64 (Landrace) to 0.74 (Slovak White Improved), which represent typical value for European breeds. Observed heterozygosity in Slovak Landrace population is equal to Korean (0.62), Vietnamese (0.60) and German population (Kim et al 2005, Thuy et al 2006. Slovak Yorkshire according to another Yorkshire population presents higher value of observed heterozygosity.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation